The Effect of Mimosa Pudica Root Extract on Cerebrum Histopathological of Rattus Norvegicus Induced with Naja Sputatrix Venom - Permatasari, Roselia Yuliani; Hestianah, Eka Pramyrtha; Legowo, Djoko; Rachmawati, Kadek; Arifin, Zainal (Universitas Airlangga, 2022)
The aim of this study was to know the effect of Mimosa pudica root extract on histopathological appearance of Rattus norvegicus brain induced by Naja sputatrix venom. Thirty rats were divided into 5 groups. There were 2 control groups and 3 treatment groups, which was given 250, 500, and 1000 mg/kg BW of Mimosa pudica root extract orally. The first 7 days each group was adapted to the environment. On the 8th day, the treatment was started by injecting Naja sputatrix LD50 (0,13 ïL/gram BW) IM in gluteus muscle, continued with giving Mimosa pudica root extract orally for the treatment groups 5 minutes after venom injection. 6 hours after the last treatment, rats were killed by cervical dislocation, injected with formalin 10% in the heart, then necropsied. Histopathological evaluation was done to score brain damage based on meningitis, perivascular cuffing, and necrotic cells using HE stain with 1000x magnification. The result showed 1000 mg/kg BW dosage of Mimosa pudica root extract can reduce brain damage based on meningitis, perivascular cuffing, and necrotic cells in Rat (Rattus norvegicus) caused by Naja sputatrix venom and gave significant difference (p < 0.05) among the treatment groups.